Maternal and foetal outcomes of patients with systematic lupus erythematosus admitted to the Maternity Ward at Groote Schuur Hospital: A retrospective study - Mbuli, Lindisa (Division of Nephrology and Hypertension, 2016)
Includes bibliographical references